Fabrication of composite ceramic polymeric membranes for agricultural wastewater treatment - Neamatalla M. Azzam; Sahar S. Ali; Gehad G. Mohamed; Mohamed M. Omar; Shereen K. Amin (Scientific Reports)
Abstract Humans have contaminated water supplies with harmful compounds, including different heavy metals. Heavy metals can interfere with human and animal vital organs and metabolic processes. They are also persistent and bioaccumulative. So, this study aimed to fabricate composite ceramic membranes (CCM) from Egyptian raw substances to eliminate heavy metals from agricultural wastewater. A ceramic supporting (CS) filter constructed from ball clay, kaolin, feldspar, and quartz using corn starch flour as a pore-developing agent. CS fired at two different temperatures and soaking times. Then, a thin polyamide 6 (PA6) coating was dip-coated over the upper layer of the support membranes. The raw materials and prepared CCM were subjected to characterization and applied to treat agricultural wastewater from the Kitchener drain in Kafr El-Sheikh Governorate, Egypt. The results showed that the CCM (M2) (membrane sintered at 1000 °C/30 min soaking time and modified with PA6) had a higher pure water permeability of 558.5 L h−1 m−2 than the membrane (M4) (membrane sintered at 1100 °C/180 min soaking time and modified with PA6). The study examined how effectively the membranes removed toxic substances from wastewater. The findings exhibited an excellent removal of > 80% and up to 97.02%, > 80% and up to 99.97% of the heavy metals, and optimum fluxes of 341.07 and 276.35 L h−1 m−2 were achieved in the cases of M2 and M4, respectively. Furthermore, with a low flux decline ratio and a high permeate recovery of 92.3% for wastewater, the modified M4 membrane demonstrated remarkable antifouling capabilities.